If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8pi = 8pi Reorder the terms: -8ip + x = 8pi Solving -8ip + x = 8ip Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-8ip' to each side of the equation. -8ip + -8ip + x = 8ip + -8ip Combine like terms: -8ip + -8ip = -16ip -16ip + x = 8ip + -8ip Combine like terms: 8ip + -8ip = 0 -16ip + x = 0 Add '-1x' to each side of the equation. -16ip + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 -16ip + 0 = 0 + -1x -16ip = 0 + -1x Remove the zero: -16ip = -1x Divide each side by '-16p'. i = 0.0625p-1x Simplifying i = 0.0625p-1x
| 3b+2a=13 | | 0.20y-0.8=0.10y+1-0.5y | | 2x^3-2x^2-24x=0 | | 5m^4-10m^3-240m^2= | | x^2-2x5=0 | | 7m-16=-17+8m | | 4k-7k=12 | | -50=9n+4 | | -3*w=-21 | | 33n=-99 | | -3(8+n)=-57 | | 8*m=-48 | | x^3-16x^2+81x-134=0 | | 27.95+-18.004+450.1= | | 5(2x-4)-3(4x+5)=97 | | ifF=77whatisC | | -5*q=20 | | -14v+-14v=-10 | | -67=6x-- | | 6x^2+96+382= | | 4*e=12 | | 2(9n-6)= | | F=77 | | 3x(2x^2+7)= | | 8(-4+r)=-112 | | 0.34*-70.6= | | 0=-16t^2+40t+12 | | 8x+2=3*x | | 1+6-(5+1)= | | a(4+3)= | | 7x-10=40x+1 | | 6x^4+5x^2-4=0 |